2019
DOI: 10.1093/her/cyz008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changes in home smoking bans on tobacco cessation among quitline callers

Abstract: Home smoking bans may be an effective way to promote tobacco cessation among treatment seeking smokers. Few studies have examined this relationship in a quitline setting. Data were obtained from 14,296 adults who were enrolled in a state quitline between January 2011 and July 2016. This study investigated whether cessation rates varied by changes in home smoking ban implementation between enrollment and 7-month follow-up. The impact of changes in home smoking bans on cessation at follow-up was significantly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Home smoking bans among treatment-seeking adults are a potentially effective way to enhance cessation rates among all household members. A prior study found that the 30-day cessation rates were highest among Quitline callers who implemented a complete household smoking ban (51%) compared to those who implemented a partial ban (27%) or no ban (14%) 14 . In the thoracic surgery and oncology context, minimizing exposure to tobacco smoke is especially important to optimize treatment outcomes for the patient, and setting home and car smoking rules might also facilitate cessation among household members.…”
Section: Discussionmentioning
confidence: 94%
“…Home smoking bans among treatment-seeking adults are a potentially effective way to enhance cessation rates among all household members. A prior study found that the 30-day cessation rates were highest among Quitline callers who implemented a complete household smoking ban (51%) compared to those who implemented a partial ban (27%) or no ban (14%) 14 . In the thoracic surgery and oncology context, minimizing exposure to tobacco smoke is especially important to optimize treatment outcomes for the patient, and setting home and car smoking rules might also facilitate cessation among household members.…”
Section: Discussionmentioning
confidence: 94%
“…34 Quit rates and harm reduction are also outcomes which will be reported as has been observed in other studies. 35,36 In order to assess the impact of the intervention on smokers perse FEV1/FEV6 was measured. This measure is a substitute for FEV1/FVC in diagnosing airflow obstruction and may better predict COPD-related pathology and morbidity.…”
Section: Revised Amendments From Versionmentioning
confidence: 99%
“…34 Quit rates and harm reduction are also outcomes which will be reported as has been observed in other studies. 35,36 In order to assess the impact of the intervention on smokers perse FEV1/FEV6 was measured. This measure is a substitute for FEV1/FVC in diagnosing airflow obstruction and may better predict COPD-related pathology and morbidity.…”
Section: Revised Amendments From Versionmentioning
confidence: 99%
“…34 Quit rates and harm reduction are also outcomes which will be reported as has been observed in other studies. 35,36 . They have been added with studies that have used them ( 33,44 ) In particular, what is the importance of measuring FeV1/FeV6 among smokers?…”
Section: Has Been Providedmentioning
confidence: 99%
See 1 more Smart Citation